Territorial planning in Central America in the XXIst. Century: common trends, originalities, and challenges - Ferrufino, Carlos (International Planning History Society Proceedings, 2016)
This paper studies the transformation processes occurred in the field of territorial planning in Guatemala, Belize, Honduras, El Salvador, Nicaragua, Costa Rica, Panama, and the Dominican Republic during the XXIst. century. All countries have undertaken major conceptual and political changes in their planning systems in the last 15 years through the approval of national planning legislation, policies, plans, and guidelines. These instruments are concerned with: environmental issues, particularly climate change adaptation and economic development. Moreover, a new Territorial Planning Agenda has emerged within the Central American Integration System (SICA) providing with a new regional framework that fosters change at the national level. Nonetheless, national particularities persist, related with different planning histories, and institutional designs. Some countries maintain predominant urban planning practices whereas others are more oriented by environmental concerns or national development strategies. In this scenario common challenges appear in terms of: institutional design, articulation between national and local levels, and addressing urgent social issues. Future perspectives for territorial planning in Central America will be related to: resolve institutional conflicts, gaps and overlaps; strength professional capabilities; consolidate the social relevance of the discipline and the pursuit of regional agendas without losing the diversity of current pluralistic approaches.